Strategi Tauke Kelapa Sawit dalam Mempertahankan Klien di Desa Pasir Emas Kecamatan Singingi Kabupaten Kuantan Singingi - Iirna Andriyanti; Yusmar Yusuf; Resdati Resdati (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2024)
The condition of oil palm fruit in Pasir Emas village has decreased in quantity or commonly referred to as